Pre-referral management of preeclampsia with severity features in a low-income country-characteristics and challenges in a Sub-Saharan setting: a mixed method studyAJOG Global Reports at a Glance - Abraham Fessehaye Sium, MD; Abrham Getachew, MPH; Wondimu Gudu, MD, MPH (Elsevier, 2024)
BACKGROUND: Preeclampsia continues to be a major cause of maternal and perinatal mortality and morbidity globally. Although pre-referral treatment constitutes a bigger part of the management package for preeclampsia with severity features in low-income settings, little is known regarding the characteristics and challenges of preeclampsia pre-referral and referral management in the Sub-Saharan setting. OBJECTIVE: To determine the characteristics and challenges of pre-referral and referral management of preeclampsia with severity features. STUDY DESIGN: We conducted a mixed method study on the pre-referral management of pregnant women complicated by preeclampsia with severity features in Ethiopia. We prospectively collected data on clinical characteristics, management outcomes, and pre-referral characteristics of pregnant women who are complicated by preeclampsia with severity features. Data were collected using a structured questionnaire. For the qualitative part of our study, we conducted 20-30 minutes of semistructured, qualitative, face-to-face, in-depth interviews with 14 health professionals. Quantitative data were analyzed using SPSS (version 23), and simple descriptive statistics were employed. We used thematic analysis on Open Code 4.03 software to analyze the qualitative data. RESULTS: A total of 261 pregnant women who had preeclampsia with severity features were included in the study, and 14 care providers were interviewed about existing challenges with pre-referral management for patients with preeclampsia with severity features. The mean systolic and diastolic blood pressures were 154.3 mm Hg and 100.3 mm Hg, respectively. The total perinatal mortality was 6.5% (17/261). Three of 261 mothers (1.1%) were complicated by intracranial hemorrhage, and other 1.1% (3/261) of other women developed pulmonary edema. Out of 261 patients, only 41 patients (15.7%) received magnesium sulfate before referral. Similarly, antihypertensive medication was given only to 35 of 261 patients (13.4%) pre-referral. Eight of 261 mothers convulsed (3.1%) during referral. Two of 261 mothers (0.8%) developed pulmonary edema when they arrived at recipient health institutions after referral. Similarly, another 2 of 261 (0.8%) women developed disseminated intravascular coagulation by the time of arrival from the referring health institution. On the basis of qualitative data analysis, 3 overarching themes were recognized: (1) challenges related to patient and family resistance, (2) Challenges related to healthcare providers' knowledge, skill, and confidence, and (3) health system-related challenges. Low use of magnesium sulfate and antihypertensive drugs, patient misperceptions regarding reasons for referral, providers' lack of knowledge on the pre-referral management, inadequate communication between referring and recipient health institutions, and nonexistence of uniform preeclampsia pre-referral and referral management protocols among the referring institutions were the identified gaps. CONCLUSION: We found a significant gap in pre-referral management for patients with preeclampsia with severity features. Preeclampsia management policy reforms should include the introduction of adequate patient counseling platforms, increasing community awareness creation, providing in-service training on pre-referral management of preeclampsia for health personnel, ensuring constant availability of anticonvulsant and antihypertensive drugs and uniform implementation of preeclampsia pre-referral management protocols across health institutions.